Analysis of the adoption of agricultural innovations in quinoa producers from Cabana, Puno (Peru) - Tudela, Juan Walter (2021)
The main objective of the research was to characterize the innovation network and estimate an innovation adoption rate to evaluate its relationship with income generation in quinoa producers in Cabana. The characterization of the innovation network has been carried out using the social network analysis methodology (SNA), the innovation adoption index (IAI) has been obtained through an ordinal measurement scale and the return of the level of adoption of innovations on Producers' income has been estimated using the two-stage least squares methodology (TSLS) through the data obtained in a survey of 268 producers. The weak articulation of social capital has been evidenced in Cabana quinoa producers; however, the network of customers and input suppliers is well defined. Most of the producers stand out for their innovations in the productive component, the main weakness is related to the scarce innovation in the administration component. For each level of innovation adopted, a return of 49.09% on the income of the producer has been estimated, showing that the adoption of innovations has a greater impact on the generation of economic income compared to the years of schooling that only reaches 7.8%.